Delayed Rebound of Glycemia During Recovery Following Short-Duration High-Intensity Exercise: Are There Lactate and Glucose Metabolism Interactions? - Messonnier, Laurent A.; Chatel, Benjamin; Emhoff, Chi-An W.; Blervaque, Léo; Oyono-Enguéllé, Samuel (Frontiers in Nutrition, 2021)
Lactate constitutes the primary gluconeogenic precursor in healthy humans at rest and during low-intensity exercise. Data on the interactions between lactate and glucose metabolisms during recovery after short-duration high-intensity exercise are sparse. The aim of the present study was to describe blood glucose ([glucose]b) and lactate ([lactate]b) concentration curves during recovery following short-duration high-intensity exercise. Fifteen healthy Cameroonian subjects took part in the study and performed successively (i) an incremental exercise to exhaustion to determine maximal work rate (Pmax) and (ii) a 2-min 110% Pmax exercise after which blood lactate and glucose concentrations were measured during the 80-min passive recovery. In response to the 2-min 110% Pmax exercise, [glucose]b remained stable (from 4.93 ± 1.13 to 4.65 ± 0.74 mmol.L−1, NS) while [lactate]b increased (from 1.35 ± 0.36 to 7.87 ± 1.66 mmol.L−1, p < 0.0001). During recovery, blood lactate concentrations displayed the classic biphasic curve while blood glucose concentrations displayed a singular shape including a delayed and transitory rebound of glycemia. This rebound began at 27.7 ± 6.2 min and peaked at 6.78 ± 0.53 mmol.L−1 at 56.3 ± 9.7 min into recovery. The area under the curve (AUC) of [lactate]b during the rebound of glycemia was positively correlated with the peak value of glycemia and the AUC of [glucose]b during the rebound. In conclusion, the delayed rebound of glycemia observed in the present study was associated with lactate availability during this period.